Manajemen Pengembangan Sumber Daya Manusia Pendidik dalam Lembaga Pendidikan Islam di Madrasah Ibtidaiyah Swasta Ikhwanul Muslimin II Tembung - Siahaan, Amiruddin; Arsita, Dhea; Lestari, Inda; Arif, M. Fadlan Fadillah; Nazah, Nadiah (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the management of educator human resource development in Islamic educational institutions in the Ibtidaiyah Private Madrasah Ibtidaiyah Muslim Brotherhood II Tembung. This type of research uses a qualitative descriptive approach. In this qualitative research, the researcher used three data collection techniques, namely interview techniques, observation techniques, and documentation techniques. The data analysis in this study uses qualitative descriptive research analysis that only collects, writes, and concludes responses from the sources obtained. The analysis is carried out with the stages of data reduction, data presentation, and decision-making. The results of the analysis show that the planning for the development of Human Resources (HR) for educators at Madrasah Ibtidaiyah Private Ibtidaiyah Muslim Brotherhood II Tembung has been running as it should, but it takes time and a process of supervision and improvement that is carried out continuously to be better in the future. In addition, the planning for the development of human resources for educators in madrasas starts from the social competence of teachers